Failure Mode and the Prevention and Control Technology of Buried PE Pipeline in Service: State of the Art and Perspectives - Pengcheng Li; Fei Wang; Jiajia Gao; Dong Lin; Jian Gao; Jianguo Lu; Enxi Qiu; Chang Liu (Advances in Civil Engineering)
Material defects and external environmental factors increase the engineering safety risks of buried PE pipelines in service. This paper mainly reviews the failure mode and the prevention and control technology of buried PE pipelines in service, as well as comparative failure characteristics between the buried PE and steel pipelines. The main failure factors of buried PE pipelines can be divided into four levels: the first level is third-party damage; the second level includes three failure factors, i.e., surface subsidence, joint failure, and aging failure; the third level consists of pipe piercing, crack development, and pipeline defect; the fourth level is a corrosion failure. Besides, steel and PE pipelines have various physical and mechanical properties, which lead to a significant difference in the service performance and degradation mechanism in practice. For instance, corrosion and welded joint leakage are the two common problems in steel pipelines during the service period, while PE pipelines have excellent corrosion resistance. Additionally, in order to ensure and maintain the long-term operations of PE pipelines, it is of great significance to develop and promote nonexcavation technologies of construction, renewal, and repair for natural gas-buried PE pipelines. Furthermore, based on the above studies, some further research studies on buried PE pipelines in service are suggested and discussed, e.g., (a) the service performance and degradation mechanism of buried PE pipelines in complicated environmental conditions, (b) the interaction mechanism among the engineering structure, PE pipelines, and geological environment, as well as PE pipeline geological soils coupled in multiple physical fields, and (c) the combinations of the traditional engineering risk assessment method and the numerical analysis method considering the interaction between the PE pipeline and geological environment. The results could be helpful for a better understanding of the operation conditions of buried PE pipelines, and it is also hoped that this study could provide guidance for the safe operation, maintenance, and integrity management of buried PE pipelines.